Simple and sensitive high performance liquid chromatographic method for the simultaneous quantitation of the phenylalanine in human plasma - Hossein Danafar (Pharmaceutical and Biomedical Research, 2015)
Phenylalanine (Phe) is the most reliable indicator for the diagnosis of phenylketonuria (PKU). The purpose of this study is to establish a reliable and quick method for the assignment of Phe in peripheral capillary blood from newborns and children by high performance liquid chromatography with ultraviolet detection (HPLC-UV). PKU is an inborn error of metabolism characterized by the inability of the body to use Phe. A rapid and sensitive high performance liquid chromatographic (HPLC) method has been developed for determination of Phe in plasma. The method uses a protein precipitation step with sulfosalicilic acid for sample preparation by separation on a Nova-pack C18 column using sodium acetate buffer and acetonitrile (94: 6 v/v) adjusted to pH 6.5 with glacial acetic acid. The eluted peaks detected by a UV detector was set at wavelength of 215 nm. The method was validated in the range of Phe concentrations from 0.1 to 20 µg/ml. The limits of detection (LOD) and quantitation (LOQ) of the method were 0.05 and 0.1 µg/ml, respectively. The average drug recovery from plasma was 88.60 percent throughout the linear concentration range., with the average within-run and between-run accuracy values of 103.3 and 115.350, respectively. The method is quick, easy, very steady and precise for the screen, assignment, and evaluation of Phe in human plasma by HPLC, which is particularly a useful way for screening and diagnosis of PKU and monitoring of a diet therapy.